Research on comprehensive assessment of regional renewable energy consumption in the electricity market environment - Cai, Qiuna; Dong, Kai; Wu, Guobing; Lu, En; Chen, Zhongfei; Li, Yupeng; Jing, Zhaoxia (2024 6th International Conference on Energy, Power and Grid (ICEPG), 2024)
Building a new power system with renewable energy as the main body is a key measure and inevitable requirement to help achieve the goals of carbon peaking and carbon neutrality. The electricity market is an essential source of support for the construction of new power systems. Research on the role of renewable energy in the assessment of the electricity market environment consumption is of great significance. First, a threestage mathematical model of the regional electricity market evolution process is constructed, and the market equilibrium at each stage is solved. Then, based on the Q-learning reinforcement learning algorithm, a multi-agent market clearing model regarding the subject's quotation strategy under imperfect competition was established, and an evaluation system including multi-dimensional indicators such as renewable energy consumption space and adequacy was built. Finally, standard node examples are used to systematically analyze carbon emission models, market equilibrium results, renewable energy consumption, multi-agent simulation, and other scenarios under different regional electricity market evolution stages, providing feasible policy suggestions for the problems.